0108 Characterisation of Wet Work and Glove Use in Healthcare Occupations. (23rd June 2014) - Humann, Michael; Virji, Abbas; Liang, Xiaoming; Stanton, Marcia; Stefaniak, Aleksandr; Henneberger, Paul
Abstract : Objectives: Wet work (contact and/or use of liquids) could lead to skin exposures to chemical irritants and sensitizers among healthcare workers. The objective of this study was to characterise the frequency and duration of glove use when wet work was performed by healthcare workers. Method: Direct observational studies were conducted from 2009 to 2011 at five hospitals on selected healthcare occupations. Information on tasks, chemical product use, and glove use was collected at five-minute intervals by trained research technicians using a standardised data collection form. Results: Between five and 51 person-days were observed for each occupation. Any glove use during wet work ranged from 62% to 100% of person-days for occupations with more than 10 person-days observed. Endoscopy technicians had the highest proportion of time of glove use when wet work was observed (1845/2055 min = 90%), followed by medical equipment preparers, dental assistants, and housekeepers (1645/1950 min = 84%, 315/395 min = 80%, and 6090/7720 min = 79% respectively). Floor strippers/waxers (585/1225 min = 48%), respiratory therapists (65/160 min = 41%), and clinical laboratory technicians (10/60 min = 17%) had lower proportions of time of glove use. When a sensitizer was used during wet work, the proportion of time of glove use increased among all healthcare occupations with adequate data. Conclusions: This analysis demonstrates that the duration of wet work and glove use vary by healthcare occupation. This assessment will be valuable for developing health and safety training programs and identifying possible avenues for intervention.